EFFECT OF LIPIDS ON PHYSICOCHEMICAL PROPERTIES OF LETROZOLE LOADED SOLID LIPID NANOPARTICLES (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
The objective of the current investigation was to prepare solid lipid nanoparticles (SLNs) from different lipids and to study the effect of lipids on physicochemical characteristics of letrozole loaded SLN. In order to prepare small, stable, uniform and high Letrozole loaded SLNs, many factors such as lipid and stabilizer concentration and preparation parameters can be considered. Out of these, we have selected solid lipid as lipid matrix to investigate an effect on SLNs. SLNs were prepared using different lipids by modified hot sonication method. The effect of different lipids and stabilizers on physicochemical characteristics of Letrozole loaded SLNs were investigated. Letrozole loaded SLNs showed different physicochemical properties and release profiles according to used solid lipid. In case of particle size, SLN1 showed biggest particle size (532.5 ± 26.4nm) and highest encapsulation efficiency (81.37 ± 6.72%) and, SLN4 showed highest cumulative drug percentage (89.4 ± 1.8%, 24 h) release. These results suggest that lipids type affect physicochemical properties and release profile of SLN. The choice of lipid and stabilizer played important role on the physicochemical characteristics and in vitro release of Letrozole loaded SLNs.